2022
DOI: 10.1007/s13132-021-00886-8
|View full text |Cite|
|
Sign up to set email alerts
|

IT Capability, Organisational Learning and Innovation Performance of Firms in Kenya

Abstract: This paper explores the role that IT capability (IT-c) plays in firm innovation performance through the channel of organisational learning (OL) in Kenya. It frames OL in two dimensions: explorative and exploitative OL. The former entails seeking new knowledge, which mainly exists outside the firm’s competence. The latter is an activity or process that builds on existing competence and knowledge in the firm. Using mediation analysis of 481 firms drawn from the World Bank Enterprise Survey (2013) and Innovation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Such practices also encourage openness in different perspectives and a wide range of new ideas in workgroups (Sancho-Zamora et al, 2022). Furthermore, Otioma (2022) revealed a significant association between team orientation, organizational performance and innovativeness.…”
Section: Learning Orientationmentioning
confidence: 95%
“…Such practices also encourage openness in different perspectives and a wide range of new ideas in workgroups (Sancho-Zamora et al, 2022). Furthermore, Otioma (2022) revealed a significant association between team orientation, organizational performance and innovativeness.…”
Section: Learning Orientationmentioning
confidence: 95%
“…The bulkiness of physical files also puts pressure on office space and thereby leading to unnecessary increase in expenditure on acquisition of more physical office space and it also brings a challenge of access to information by management and staff thereby impeding smooth operations which negatively affects the performance of the Shipyards (Otioma, 2022).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…KSL, SECO and AMGECO are all connected to high speed fibre internet and the Shipyards have laid the necessary IT infrastructure to facilitate seamless operations. Management information systems in this 21 st century .is therefore a necessary investment by firms who want to compete at high levels (Otioma, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The organisational learning climate characterised by shared beliefs, attitudes, and conventions that promote learning, information exchange, and continuous development among employees, significantly influences technology adoption in businesses which enhancing their performance and outputs (Migdadi, 2021). Organisational learning encompasses investigation (seeking external knowledge) and utilisation (leveraging internal knowledge), and it serves as a crucial link in the business value chain, enabling organisations to acquire market knowledge, adapt to changes, and achieve flexibility (Chuks, 2022;Jiménez-Jiménez & Sanz-Valle, 2011). Previous research has shown that corporate learning capacity positively impacts turnover and earnings.…”
Section: Organisational Learning Climatementioning
confidence: 99%